Occurrence of photoluminescence and onion like structures decorating graphene oxide with europium using sodium dodecyl sulfate surfactant. (10th July 2017) - Cedeño, V J; Rangel, R; Cervantes, J L; Lara, J; Alvarado, J J; Galván, D H
Abstract: Graphene oxide decoration with europium was carried out using SDS (sodium dodecyl sulfate) as the surfactant. The reaction was performed in a microwave oven and subsequently underwent thermal treatment under hydrogen flow. The results found in the present work demonstrate that through the use of SDS surfactant aggregates of hemi-cylindrical and onion-like structures could be obtained; which propitiate an enhanced synergistic photoluminescence located at the red wavelength. On the other hand, after thermal treatment the aggregates disappear providing a good dispersion of europium, however a decrease in the photoluminescence signal is observed. The graphene oxide decorated with europium was characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Fourier infrared transform spectroscopy (FTIR), RAMAN spectroscopy, x-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) techniques, showing the characteristic features of graphene oxide and europium.